2015
DOI: 10.7150/ijbs.10178
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Follicular Helper T Cells in Idiopathic Thrombocytopenic Purpura Patients

Abstract: Background: Idiopathic thrombocytopenic purpura (ITP) is a primary autoimmune disease with a decreased platelet count caused by platelet destruction mediated mainly by platelet antibodies. T follicular helper (TFH) cells have demonstrated important roles in autoimmune diseases. The aim of this study is to explore the might role of TFH cells in the patients of ITP.Methods: Twenty-three ITP patients and 12 healthy controls (HC) were enrolled in this study. The frequency of circulating TFH cells in both the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 43 publications
1
34
1
Order By: Relevance
“…Interestingly, these are autoantibody-mediated autoimmune diseases. Furthermore, studies have showed both an expansion of cT FH cells and an association with the autoantibody titers in these autoimmune diseases [32][33][34]. In the present study, CVID patients with autoimmune diseases showed increased, but not significant, proportion of cT FH cells.…”
Section: Discussionsupporting
confidence: 46%
“…Interestingly, these are autoantibody-mediated autoimmune diseases. Furthermore, studies have showed both an expansion of cT FH cells and an association with the autoantibody titers in these autoimmune diseases [32][33][34]. In the present study, CVID patients with autoimmune diseases showed increased, but not significant, proportion of cT FH cells.…”
Section: Discussionsupporting
confidence: 46%
“…Tfh cells have been identified by phenotypic profile, co‐expressions of the chemokine receptor CXCR5, costimulatory molecules ICOS and programmed cell death protein‐1 (PD‐1) . Several reports consider dysfunctional Tfh cells may play an important role in the pathophysiology of autoimmune disease, such as rheumatoid arthritis, autoimmune thyroid diseases and immunothrombocytopenia .…”
Section: Introductionmentioning
confidence: 99%
“…Tfh subset, which regulates B-cell responses and stimulates antibody production, is increased in ITP patients [8]. Splenic Tfh expansion participates in B-cell differentiation and antiplateletantibody production during ITP by IL-21 secretion and CD40/ CD40 L interaction [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, novel approaches of platelet destruction have been identified in ITP (e.g., direct lysis of platelet by CTLs [4] and hepatic clearance of desialylated platelets) [5]. Many cellular mechanisms of immune modulation have been described in patients with ITP, such as increased number of Th1 [6], Th17 [7], and Tfh [8], and decreased number or defective suppressive function of Treg [9].…”
Section: Introductionmentioning
confidence: 99%